Workplace factors associated with willingness to undergo human immunodeficiency virus testing during workplace health checkups - Kazuyoshi Mizuki; Tomohiro Ishimaru; Mayumi Imahashi; Yuzuru Ikushima; Hideto Takahashi; Masashi Masuda; Yoshiyuki Yokomaku (Komiyama Printing Co. Ltd, 2023)
Background: To examine workplace factors associated with willingness to undergo human immunodeficiency virus (HIV) testing during workplace health checkups. Methods: This cross-sectional study used an Internet-based self-administered questionnaire to obtain data from a pool of 24,287 Japanese workers. Binary and multiple logistic regression analyses evaluated the association between workplace factors and HIV testing. Data were adjusted for sex, age, marital status, education, and history of HIV testing. Results: We gathered information from 4,143 (17.1%) respondents, of whom 1,129 (27.3%) were willing to be tested for HIV as part of a workplace health checkup. The participants were 20-59 years old. Approximately half of the participants were male (49.9%), half were married (48.9%), and half had completed higher education (47.6%). Workplace hepatitis testing was offered to 15.6% of the respondents, and most participants underwent health checkups without their colleagues (52.1%) at a medical facility (60.2%). Willingness to undergo HIV testing was positively correlated with having an increased risk of occupational blood exposure (vs. not at risk, adjusted odds ratio [OR]: 1.74, 95% confidence interval [CI]: 1.41-2.15) or working in medical and welfare roles (vs. manufacturing, OR: 1.40, 95% CI: 1.07-1.84). The presence of occupational health staff at the workplace (vs. their absence, adjusted OR: 1.35, 95% CI: 1.16-1.59) and hepatitis testing (vs. not testing, adjusted OR: 2.02, 95% CI: 1.66-2.44) increased willingness to undergo HIV testing. Conclusions: A pilot HIV-testing program involving individuals at an increased risk of occupational blood exposure and undergoing hepatitis tests in workplaces providing occupational health staff support is recommended.